Increased Angiogenin Expression Correlates With Radiation Resistance and Predicts Poor Survival for Patients With Nasopharyngeal Carcinoma - Guo, Shan-Shan; Liang, Yu-Jing; Liu, Li-Ting; Chen, Qiu-Yan; Wen, Yue-Feng; Liu, Sai-Lan; Sun, Xue-Song; Tang, Qing-Nan; Li, Xiao-Yun; Mai, Hai-Qiang; Tang, Lin-Quan (Frontiers in Pharmacology, 2021)
Background: Despite the development of such multiple therapeutic approaches, approximately 20% patients experience recurrence. Identification of molecular markers for stratifying the different risks of tumour recurrence and progression is considered imperative. Methods: We used a RayBio Human Cytokine Antibody Array that simultaneously detected the levels of 297 proteins and profiled the conditioned medium of HONE1 cells and the radioresistant NPC cells HONE1-IR. We found ANG expression to be significantly increased in HONE1-IR and HONE1-IR cells exposed to 4-Gy X-ray radiation. Results: Subsequently, we investigated the expression of ANG in NPC tissues and explored its prognostic significance in patients with NPC. We found that ANG expression was increased in recurrent NPC tissues. Elevated expression of ANG induced radio-resistance in NPC cells, in addition to being significantly associated with shorter PFS, OS, and LRFS in patients with NPC. Multivariate analysis results revealed that ANG was an independent prognostic factor that predicted PFS, OS, and LRFS. Furthermore, a nomogram model was generated to predict OS in terms of ANG expression. Conclusions: Our results found the radioresistant function of ANG and proved the clinical prognostic significance of ANG, and the results could help predict radio-sensitivity and stratify high-risk patients or tumour recurrence.